Pengaruh Kadar Air Terhadap Pengembangan Tanah Ekspansif - Adang Irawan; Tiorivaldi Tiorivaldi (Jurnal Rekayasa Infrastruktur, 2023)
Expansive soil is one type of problematic soil, very sensitive to changes in moisture content. This soil has the characteristics of large shrinkage expansion due to changes in pore volume which can cause lifting forces on existing construction can cause damage to the construction. This research aims to determine the effect of water content on expansive soil in increasing the percentage of swelling soil. The research was conducted experimentally with materials used in this test is expansive soil taken from Sambungmacan, Sragen, Central Java. The main test equipment used in this test is a steel cylindrical mould. Cylindrical mould is filled with expansive soil then compacted a depth of 12 cm. Then the expansive soil is gradually moistened with water until it reaches maximum moisture content to determine its effect on the swelling value. The results of this study show that the increasing water content, then swellin percentage increases in expansive soils until the soil no longer expands at a certain water content.